2019
DOI: 10.1016/j.ynstr.2019.100179
|View full text |Cite
|
Sign up to set email alerts
|

Chronic unpredictable stress influenced the behavioral but not the neurodegenerative impact of paraquat

Abstract: The impact of psychological stressors on the progression of motor and non-motor disturbances observed in Parkinson's disease (PD) has received little attention. Given that PD likely results from many different environmental “hits”, we were interested in whether a chronic unpredictable stressor regimen would act additively or possibly even synergistically to augment the impact of the toxicant, paraquat, which has previously been linked to PD. Our findings support the contention that paraquat itself acted as a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 53 publications
0
19
0
Order By: Relevance
“…The most obvious feature of CMS that the animals manifest is anhedonia [ 106 , 107 ], demonstrated by sucrose intake and preference, which is reversed by chronic, but not by acute, antidepressant treatment [ 110 ]. Rodents exposed to CMS also exhibited hyperlocomotion in the open field test [ 107 ], shorter time spent in the open arm in EPM [ 108 ], and prolonged immobility time in the FST [ 109 ]. The CMS paradigm induces altered regulation of the hypothalamus–pituitary–adrenal (HPA) axis, changes in serotonergic, noradrenergic and dopaminergic systems, and reduced hippocampal BDNF level (details are reviewed by Hill et al) [ 111 ].…”
Section: Models Of Depressionmentioning
confidence: 99%
See 1 more Smart Citation
“…The most obvious feature of CMS that the animals manifest is anhedonia [ 106 , 107 ], demonstrated by sucrose intake and preference, which is reversed by chronic, but not by acute, antidepressant treatment [ 110 ]. Rodents exposed to CMS also exhibited hyperlocomotion in the open field test [ 107 ], shorter time spent in the open arm in EPM [ 108 ], and prolonged immobility time in the FST [ 109 ]. The CMS paradigm induces altered regulation of the hypothalamus–pituitary–adrenal (HPA) axis, changes in serotonergic, noradrenergic and dopaminergic systems, and reduced hippocampal BDNF level (details are reviewed by Hill et al) [ 111 ].…”
Section: Models Of Depressionmentioning
confidence: 99%
“…Induces both anxiety- and depression-like behaviors in FST, EPM, and sucrose preference tests [ 104 , 105 , 106 , 107 , 108 , 109 ].…”
Section: Tablementioning
confidence: 99%
“…The rotarod test and increased signs of anhedonia (sucrose preference test), where paraquat-treatment induced some non-motor symptoms in open-field, Y-maze, and plus-maze test defects without significant signs between the group of mice. They suggested that there is no interaction (additive or synergistic) between chronic unpredictable stress exposure and paraquat on behavioral and non-motor behavioral effects (except the rotarod test and 5th week of sucrose preference) [ 179 ]. Cristóvão et al (2020) administered paraquat 2.5 mg/kg/day, subcutaneously (osmotic minipump implanted in the back with 0.25 µL/h fluid delivery rate) for four weeks in male Wistar rats.…”
Section: Neurotoxins Used To Induce Pd In Vivo Modelsmentioning
confidence: 99%
“…Obese and diabetic animals show depression-like behaviors [ 90 , 91 , 92 ], which could be partly contributed by impaired hippocampal adult neurogenesis [ 93 , 94 , 95 ]. Both rodent models of depression [ 96 , 97 , 98 , 99 ] and diabetes [ 100 , 101 , 102 ] have shown a hyper-activated hypothalamic-pituitary-adrenal (HPA) axis, resulting in elevated glucocorticoid levels in response to stressors. The hippocampus exerts inhibitory feedback control to the activation of the HPA axis through GABAergic innervation to the paraventricular nucleus (PVN) of the hypothalamus [ 103 , 104 , 105 ].…”
Section: Introductionmentioning
confidence: 99%